Report of meetings of the representatives of I.F.T.U. executive and L.S.I. Bureau, held in Geneva , 16th and 17th June, 1937
016a-0014-001 PRIVATE AND CONFIDENTIAL NATIONAL COUNCIL OF LABOUR and G.C. 3/12/1936-37. 22nd JUNE, 1937 REPORT OF MEETINGS OF THE REPRESENTATIVES OF I.F.T.U. EXECUTIVE AND L.S.I. BUREAU, HELD IN GENEVA , 16th AND 17th JUNE, 1937. At the request of the Spanish Comrades a Joint Meeting of the I.F.T.U. Executive and the L.S.I. Bureau was held in Geneva on the 16th and 17th June. There were present:- For the I.F.T.U. - Messrs. Hayday, Jouhaux, Schevenels (General Secretary). For the L.S.I. - Messrs. de Brouckere, Gillies, Longuet, Zyromski. For the Spanish Trade Unions: Messrs. Pascual Tomas, Vidal Rossell, Rodriguez Vega. For the Spanish Socialist Party. - Mme. Palencia, Mr. F. Azorin. There were also present Messrs. C. Mertens and Bondas (Belgium), and W.J. Bolton. in the Chair - Mr. L. de Brouckere. After a long discussion, during which the Spanish Comrades stated that in addition to the fact that troops and arms had arrived in the Basque country recently, the bombardment of Almeria constituted direct intervention, the following resolution was agreed:- "The representatives of the I.F.T.U. and the L.S.I., meeting in Geneva on 16th and 17th June: "Declare that the breakdown of the system of control, which is now obvious, makes it more than ever the duty of the Internationals, in conformity with the London resolution of the 19th March, to appeal to all the peoples of the world, to bring to an end by all the means in their power the policy of permanent and large-scale intervention, which is being practised by Italy and Germany, under the guise of the policy so inaptly called non-intervention; "declare moreover that the delay which has occurred in the withdrawal of non-Spanish combatants (which was declared by the last Council meeting of the League of Nations to be an urgent question) is favourable to the aims pursued in Spain by Italy and Germany; and "consider that the responsible organs of the I.F.T.U. and the L.S.I. should meet without delay to determine how effect should be given to the resolution adopted at London by the Joint Conference of these two Internationals." EAB/EKK/466. 292/946/16a/16